Peran Pertumbuhan Ekonomi Dan Penerimaan Dalam Negeri Pada Tingkat Kebahagiaan Masyarakat Dengan Ketimpangan Sebagai Variabel Mediasi - Widhi Ariestianti Rochdianingrum; T Triyonowati; S Suwitho (Akademi Akuntansi YKPN Yogyakarta, 2023)
Research on happiness is mostly done in terms of psychology. In this study, the level of happiness is seen from the sosial and economic side. The purpose of this study is to find out how the influence of economic growth and domestic income in influencing the level of happiness with inequality as a mediating variable. The data used in this study is secondary data obtained from BPS in 2009-2020. Hypothesis testing was carried out using PLS. From the results of the study it is known that domestic income acceptance has an influence on happiness. Domestic income, which is used more for spending to meet the level of community welfare, such as the establishment or improvement of the quality of community facilities such as health and education facilities, can help the community in improving the quality of life and values that exist within them so that the opportunity to participate in economic activities increases. So that the income received by the community is getting bigger so that the community's ability to meet the needs of the community is increasing. This condition can increase the level of happiness. The level of inequality cannot bridge the influence of economic growth and domestic income on happiness. This is because whatever the economic conditions and the situation of state revenues, the government always tries to increase the distribution of income so that the level of inequality decreases. Inequality and gross domestic product do not have a direct influence on determining the level of happiness.